2011
DOI: 10.1063/1.3639291
|View full text |Cite
|
Sign up to set email alerts
|

12% efficient CdTe/CdS thin film solar cells deposited by low-temperature close space sublimation

Abstract: We report 12% efficient CdS/CdTe thin film solar cells prepared by low temperature close space sublimation (CSS). Both semiconductor films, CdS and CdTe, were deposited by high vacuum CSS in superstrate configuration on glass substrates with fluorine doped tin oxide (FTO) front contact. The CdTe deposition was carried out at a substrate temperature (Tsub) of 340° C, which is much lower than that used in conventional processes (>500 ° C). The CdTe films were treated with the usual CdCl 2 activation process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 18 publications
(27 reference statements)
0
23
0
Order By: Relevance
“…Numerous reports [21][22][23][24][25][26] conclude that the XRD peaks observed show recrystallisation and grain growth after CdCl 2 treatment. Heat treatment alone, without CdCl 2 , also shows this trend, but the presence of CdCl 2 enhances the recrystallisation.…”
Section: Recrystallisation and Grain Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports [21][22][23][24][25][26] conclude that the XRD peaks observed show recrystallisation and grain growth after CdCl 2 treatment. Heat treatment alone, without CdCl 2 , also shows this trend, but the presence of CdCl 2 enhances the recrystallisation.…”
Section: Recrystallisation and Grain Growthmentioning
confidence: 99%
“…However, some research groups have reported that as-grown CdTe layers have (111) preferred orientation but after CdCl 2 treatment, the intensity of the (111) peak reduces and the other two peaks (220) and (311) become visible and the material therefore loses the preferential orientation along the (111) plane and becomes poly-crystalline [20][21][22][23][24][25][26][27]. There are also reports concluding that there is no grain growth if the starting CdTe layer has large grains [9].…”
Section: Recrystallisation and Grain Growthmentioning
confidence: 99%
“…Hadrich et al (2007) produced CdS/CdTe based solar cell which shows efficiency s = 8.2% with V oc = 0.68 V, J sc = 21.3 mA cm −2 , and ff = 0.57. Seymour (2005) produced CdTe based solar cells treated with Cu, having an efficiency s = 12.4% with V oc = 0.82 V, J sc = 23.9 mA cm −2 and ff = 0.63 and Jvdith (Schaffner et al, 2011) shows efficiency 12% by using copper in CdTe. Razkov also shows the latest evaluation of the conversion efficiencies of various type of research PV Cells (Razkov et al, 2011).…”
Section: Sr Nomentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Also, chalcopyrite I-III-VI 2 compounds have recently attracted attention as potential components for semiconductor devices, including applications in solar cells and electrooptic devices. [8][9][10] In particular, CuInSe 2 has already become widely used in making commercial solar cells.…”
Section: Introductionmentioning
confidence: 99%